Parental knowledge, attitude, and practice on pediatric pneumonia in Beijing, China: a cross-sectional study. - Hao, Qiaoxin; Yan, Peng; Guo, Wei; Ren, Jie; Li, Qiong; Zhang, Pei; Huang, Chenghe; Gu, Jiangying (Journal of Public Health: From Theory to Practice (2198-1833), 2025)
Aim: Pediatric pneumonia, a common disease, is the major cause of mortality in young children in China. However, the knowledge, attitude, and practice (KAP) of parents in China on etiologies, prevention, and care of pediatric pneumonia are still unclear. Here we investigated the KAP of parents on pediatric pneumonia. Subject and methods: This cross-sectional study enrolled parents in the Yungang area, Fengtai, Beijing and surrounding areas from September 1, 2022 to October 31, 2022. The demographic characteristics of subjects were collected for KAP score evaluation. The KAP scores of parents with different demographic characteristics were compared. Results: In total, 502 subjects participated in this study, of which the mean knowledge score was 9.61 ± 3.25, the attitude score was 33.85 ± 4.03, and the practice score was 17.87 ± 2.38. The findings showed that gender, age, residence, education, medical-field work, income per capita, previous pediatric pneumonia, and smoking significantly differed in knowledge score (P < 0.05). Gender, residence, education, and previous pediatric pneumonia were significantly different in attitude score (P < 0.05). Parental age, children's numbers, and smoking were significantly different in practice score (P < 0.05). Conclusion: Parents of young children exhibit a good attitude and practice toward prevention and treatment of pediatric pneumonia, while the relevant knowledge about the same disease was lower. It was recommended to carry out further studies in different regions; government and health institutions could take steps to improve the KAP of parents.